Friction coefficient model and joint formation in rotary friction welding. (October 2019) - Jin, Feng; Li, Jinglong; Liu, Pu; Nan, Xujing; Li, Xun; Xiong, Jiangtao; Zhang, Fusheng
Abstract: Rotary Friction Welding (RFW) was conducted on SUS304 and A286 stainless steels in which, the joint forming stage was focused. Pipe structure specimens were welded firstly, from which the friction coefficient models were built as functions of friction linear speed, pressure and temperature. Based on the models, the friction heat distributions and temperature fields of rod structure specimens at different rotation speeds were characterized. Experiments of initiation and evolution of the corona-bond (i.e., plasticized metal) were carried out to verify the theoretical results. Welding time, as an application of the model, was analyzed with the corona-bond initiation and evolution. The results show that, friction coefficient models of SUS304 and A286 as functions of friction linear speed, pressure and temperature were constructed as f S U S 304 = 0.274 ∙ P - 0.936 ∙ T - 273 0.705 ∙ e x p ⁡ ( - 0.34 v ) and f A 286 = 0.15 ∙ P - 0.405 ∙ T - 273 0.475 ∙ e x p ⁡ ( - 0.705 v ) respectively. SUS304 concentrates the friction heat at the periphery where the corona-bond is consequently initiated, which varies little with rotation speed; whereas, A286 moves the concentration from the 0.60R to the center as the rotation speed increases, which implies the initiation location of the corona-bond that consequently shifts from 0.60R to axis zone. For rod structure specimens, the joint forming time determines the welding time of the joint welded at a preset burn-off. The joint forming time falls around 5 s for SUS304, which is roughly independent of rotation speed; Whereas, for A286, the joint forming time varies from 5 s to 20 s, which increases along with the rotation speed. Thus, both materials of RFW cover different welding time at a preset burn-off of 5 mm when the rotation speed changes from 500 rpm to 2000 rpm: SUS304 varies from 14 s to 18 s and A286 from 23 s to 35 s.